2010
DOI: 10.1042/bst0381448
|View full text |Cite
|
Sign up to set email alerts
|

The neuronal ceroid lipofuscinoses: the same, but different?

Abstract: The NCLs (neuronal ceroid lipofuscinoses) (also known as Batten disease) are a group of at least ten fatal inherited storage disorders. Despite the identification of many of the disease-causing genes, very little is known about the underlying disease mechanisms. However, now that we have mouse or large-animal models for most forms of NCL, we can investigate pathogenesis and compare what happens in the brain in different types of the disease. Broadly similar neuropathological themes have emerged, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…PGRN is therefore likely to be primarily implicated in lysosomal biogenesis that leads to microglial activation and microgliosis. In the present study, we showed that aged PGRNdeficient mice presented with increased accumulation of p62 and ubiquitin in the VPM/VPL, where the main pathological changes have been observed in reported NCL model mice [15][16][17][18]. p62/ubiquitin inclusions have been observed when the autophagy-lysosomal system is disrupted [26].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…PGRN is therefore likely to be primarily implicated in lysosomal biogenesis that leads to microglial activation and microgliosis. In the present study, we showed that aged PGRNdeficient mice presented with increased accumulation of p62 and ubiquitin in the VPM/VPL, where the main pathological changes have been observed in reported NCL model mice [15][16][17][18]. p62/ubiquitin inclusions have been observed when the autophagy-lysosomal system is disrupted [26].…”
Section: Discussionmentioning
confidence: 64%
“…Neurons in the VPM/VPL project to the S1BF, and both of these structures show particular vulnerability in previously reported NCL mouse models [15]. We performed Nissl staining to compare the number of viable neurons in the VPM/VPL in 10-and 90-week-old WT and KO mice.…”
Section: Pgrn Deficiency Results In Neuronal Loss In the Vpm/vpl And mentioning
confidence: 99%
See 1 more Smart Citation
“…loss of SV2 was observed in the affected motor cortex but not in the spared cerebellum). Previous studies using mouse and Drosophila models of Batten disease have revealed that synaptic disruption is intimately linked to the regional onset of neurodegeneration (Cooper 2010; Bond et al. 2013), with our findings demonstrating that the relationship between synaptic pathology and neurodegeneration is likely to be similarly conserved in CLN5 sheep.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main consequences of this is the intralysosomal buildup of material that would otherwise have been degraded (Platt, Boland, & van der Spoel, 2012;Vitner et al, 2010;Walkley, 2007). Although opinion, and experimental evidence, varies for whether this storage material is actually harmful to cells in each LSD (e.g., Cooper, 2010;Palmer, Barry, Tyynelä, & Cooper, 2013), measuring the relative level of this storage burden in tissue sections is nevertheless very informative. Such measurements are necessarily complicated by the normal turnover of cells in somatic tissues or the loss of these cells due to the effects of disease.…”
Section: Introductionmentioning
confidence: 97%